1997
DOI: 10.1074/jbc.272.20.13338
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Formation of Sodium Dodecyl Sulfate-stable Complexes between Serpins and 3,4-Dichloroisocoumarin-inactivated Proteinases Is Due to Regeneration of Active Proteinase from the Inactivated Enzyme

Abstract: Protein proteinase inhibitors of the serpin family were recently reported to form SDS-stable complexes with inactive serine proteinases modified at the catalytic serine with 3,4-dichloroisocoumarin (DCI) that resembled the complexes formed with the active enzymes (Christensen, S., Valnickova, Z., Thøgersen, I. B., Pizzo, S. V., Nielsen, H. R., Roepstorff, P., and Enghild, J. J. (1995) J. Biol. Chem. 270, 14859 -14862). The discordance between these findings and other reports that similar active site modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Enghild et al (24) thus asked whether the formation of such complexes was sufficient to accelerate clearance, and found that complexes of serpin and 3,4-dichloroisocoumarin (DCI)-inactivated serine proteinase were cleared from the murine circulation more rapidly than the corresponding native serpin. However, further studies indicated that the DCIproteinase complex decayed, releasing active proteinase which then could covalently complex with the serpin (25), effectively converting the encounter complex into an SEC. Thus, the results of in vivo clearance studies suggest that maximal acceleration of serpin clearance requires formation of covalently associated, denaturation-resistant, SEC.…”
Section: Sec Clearance In Vivomentioning
confidence: 99%
“…Enghild et al (24) thus asked whether the formation of such complexes was sufficient to accelerate clearance, and found that complexes of serpin and 3,4-dichloroisocoumarin (DCI)-inactivated serine proteinase were cleared from the murine circulation more rapidly than the corresponding native serpin. However, further studies indicated that the DCIproteinase complex decayed, releasing active proteinase which then could covalently complex with the serpin (25), effectively converting the encounter complex into an SEC. Thus, the results of in vivo clearance studies suggest that maximal acceleration of serpin clearance requires formation of covalently associated, denaturation-resistant, SEC.…”
Section: Sec Clearance In Vivomentioning
confidence: 99%
“…V 0 is the rate of change in A 405 at time zero, k off is the first-order rate constant for complex dissociation, [E Ϫ I] 0 is the starting concentration of complex, and TN is the turnover number for the hydrolysis of substrate by enzyme under the conditions of the experiment and was independently measured. Complex dissociation is irreversible because serpin is released from the complex in an inactive cleaved form rather than in the native intact form (24). The dissociation rate of the ␣ 1 -antitrypsin Add-2-factor Xa complex was too fast to be analyzed by the above method and was therefore determined by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Thrombin, factor Xa and bovine trypsin were active site titrated and found to be 70 -100% active based on comparisons with the concentrations measured from the 280-nm absorbance and published absorption coefficients (4,39). The concentrations of HNE and porcine trypsin were based on a stoichiometric titration of the enzyme with ␣ 1 PI as described (40). Proteinase concentrations were routinely determined from initial rates of proteinase hydrolysis, monitored from the absorbance change at 405 nm, of the substrates, S-2238 (Chromogenix) for thrombin, Spectrozyme FXa (American Diagnostica) for factor Xa, S-2222 (Chromogenix) for trypsin, or methoxysuccinyl-Ala-Ala-Pro-Val-p-nitroanilide (Sigma) for HNE under standard conditions after calibrating these rates using known concentrations of active site titrated proteinase.…”
Section: Methodsmentioning
confidence: 99%